Sustainability Handling Slum Settlements in Makassar City, South Sulawesi Indonesia - Batara Surya; Emil Salim; Muhammad Idris (Jurnal Ilmiah Ecosystem, 2021)
This study aims to (1) analyze the spatial integration of work as a determinant of the sustainability of the handling of slums in Makassar City; (2) analyze the direct and indirect effects of handling infrastructure, controlling environmental pollution, and socio-economic empowerment on improving the quality of slums and the sustainability of handling the slums of Makassar City. The research approach used is a sequential explanatory design, which is a combination of quantitative and qualitative research. Data obtained through observation, surveys, in-depth interviews, and documentation. The results showed that the acceleration of Makassar City development towards urban spatial integration had an impact on slum areas that developed at riverbanks and coastal areas. The results of the path analysis show that infrastructure has a direct effect on improving environmental quality by 12.46%, the direct effect of environmental pollution control on improving environmental quality by 10.69%, and the direct effect of socio-economic empowerment on handling slum settlements by 6.76%. Furthermore, the increase in Y was 63.58% and the effect of Y on Z was 67.57%. The direction of handling the Makassar City slums in the future is oriented to sustainable development including, improving the quality of infrastructure, increasing the productivity of economic ventures, increasing the capacity of government and community institutions in dealing with social problems, social conflicts, towards the creation of social cohesion, fulfillment of livable facilities that are livable and socially just.